Early Initiation of Antiretroviral Therapy Following In Utero HIV Infection Is Associated With Low Viral Reservoirs but Other Factors Determine Viral Rebound. (7th May 2021) - Millar, Jane R; Bengu, Nomonde; Vieira, Vinicius A; Adland, Emily; Roider, Julia; Muenchhoff, Maximilian; Fillis, Rowena; Sprenger, Kenneth; Ntlantsana, Vuyokazi; Fatti, Isabella; Archary, Moherndran; Groll, Andreas; et al.
Abstract: Background: Early HIV diagnosis allows combination antiretroviral therapy (cART) initiation in the first days of life following in utero (IU) infection. The impact of early cART initiation on infant viral reservoir size in the setting of high-frequency cART nonadherence is unknown. Methods: Peripheral blood total HIV DNA from 164 early treated (day 0–21 of life) IU HIV-infected South African infants was measured using droplet digital PCR at birth and following suppressive cART. We evaluated the impact of cART initiation timing on HIV reservoir size and decay, and on the risk of subsequent plasma viremia in cART-suppressed infants. Results: Baseline HIV DNA (median 2.8 log10 copies/million peripheral blood mononuclear cells, range 0.7–4.8) did not correlate with age at cART initiation (0–21 days) but instead with maternal antenatal cART use. In 98 infants with plasma viral suppression on cART, HIV DNA half-life was 28 days. However, the probability of maintenance of plasma aviremia was low (0.46 at 12 months) and not influenced by HIV DNA load. Unexpectedly, longer time to viral suppression was associated with protection against subsequent viral rebound. Conclusions: With effective prophylaxis against mother-to-child transmission, cART initiation timing in the first 3 weeks of life is not critical to reservoir size. Abstract : Peripheral blood HIV DNA levels from 164 South African in utero HIV-infected infants showed that with antiretroviral mother-to-child transmission prophylaxis, combination antiretroviral therapy initiation timing in the first 3 weeks of life does not significantly influence latent HIV reservoir size.